Crystalline quality of 3C-SiC formed by high-fluence C+-implanted Si - S. Intarasiri (2018)
Carbon ions at 40 keV were implanted into (1 0 0) high-purity p-type silicon wafers at 400 °C to a fluence of 6.5 × 1017ions/cm2. Subsequent thermal annealing of the implanted samples was performed in a diffusion furnace at atmospheric pressure with inert nitrogen ambient at 1100 °C. Time-of-flight energy elastic recoil detection analysis (ToF-E ERDA) was used to investigate depth distributions of the implanted ions. Infrared transmittance (IR) and Raman scattering measurements were used to characterize the formation of SiC in the implanted Si substrate. X-ray diffraction analysis (XRD) was used to characterize the crystalline quality in the surface layer of the sample. The formation of 3C-SiC and its crystalline structure obtained from the above mentioned techniques was finally confirmed by transmission electron microscopy (TEM). The results show that 3C-SiC is directly formed during implantation, and that the subsequent high-temperature annealing enhances the quality of the poly-crystalline SiC. © 2006 Elsevier B.V. All rights reserved.